2000
DOI: 10.1098/rspb.2000.1105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of sex–linked effects on the inheritance of human longevity: a population–based study in the Valserine valley (French Jura), 18–20th centuries

Abstract: A long-standing puzzle in gerontology is the sex dependence of human longevity and its inheritance. We have analysed the sex-linked pattern of inheritance of longevity from 643 nuclear families on the historical population register of a French valley. We have focused on mean conditional life expectancy at a minimum age of 50 years, thus, in the present study, longevity refers to late or post-reproductive survival. A comparison of parents' and o¡spring's longevity has shown the existence of a heritable componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 28 publications
4
30
1
Order By: Relevance
“…It is not surprising to observe an association between siblings' life duration, as they share about 50% of their genes. Overall, studies have indicated that a modest amount of about 25% of the variation in human lifespan may be genetically influenced, whereas almost 75% could be attributable to environmental factors (Christensen and Vaupel 1996;Herskind et al 1996;Ljungquist et al 1998;Cournil et al 2000;Kerber et al 2001). However, these studies were conducted in populations where few individuals have reached their 85th birthday.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is not surprising to observe an association between siblings' life duration, as they share about 50% of their genes. Overall, studies have indicated that a modest amount of about 25% of the variation in human lifespan may be genetically influenced, whereas almost 75% could be attributable to environmental factors (Christensen and Vaupel 1996;Herskind et al 1996;Ljungquist et al 1998;Cournil et al 2000;Kerber et al 2001). However, these studies were conducted in populations where few individuals have reached their 85th birthday.…”
Section: Discussionmentioning
confidence: 95%
“…The existence of a familial transmission and aggregation of longevity is now well established (Beeton and Pearson 1901;Bell 1918;Pearl 1931;Abbot et al 1978;Philippe 1978;Bocquet-Appel and Jakobi 1990;Cournil et al 2000;Gavrilov and Gavrilova 2001;Gavrilov et al 2002;Atzmon et al 2005;Caselli et al 2006;You et al 2010). Most research in the area has focused on the survival of relatives of individuals who reached advanced ages.…”
Section: The Familial Clustering Of Exceptional Longevitymentioning
confidence: 99%
“…Second, the grandfather variable is included as a kind of control variable in a more specific way: Since children have the same degree of relatedness to their grandfathers as to their grandmothers (for the moment assuming that social relatedness corresponds completely to biological relatedness) any difference in effects between the survival of grandmothers and grandfathers on the effect of survival of their grandchildren should reflect true behavioral causes and not potential genetic ones (ignoring here any potential sex-linked effects in heritability, e.g. Cournil, Legay, and Schächter 2000).…”
Section: The Grandfathersmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Although these studies do not distinguish between shared environmental and genetic factors, twin data suggest that genes may have a modest role in achieving longevity. 12,13 In order to better distinguish the effect of genes from the effect of shared familial environment, Schoenmaker et al 3 analyzed the survival data of the spouses of long-lived subjects as an additional control group.…”
Section: Introductionmentioning
confidence: 99%